CRISPR RNA-guided FokI nucleases repair a PAH variant in a phenylketonuria model - Pan, Yi; Shen, Nan; Jung-Klawitter, Sabine; Betzen, Christian; Hoffmann, Georg F.; Blau, Nenad (Scientific reports, 2016)
The CRISPR/Cas9 system is a recently developed genome editing technique. In this study, we used a modified CRISPR system, which employs the fusion of inactive Cas9 (dCas9) and the FokI endonuclease (FokI-dCas9) to correct the most common variant (allele frequency 21.4%) in the phenylalanine hydroxylase (PAH) gene - c.1222C>T (p.Arg408Trp) - as an approach toward curing phenylketonuria (PKU). PKU is the most common inherited diseases in amino acid metabolism. It leads to severe neurological and neuropsychological symptoms if untreated or late diagnosed. Correction of the disease-causing variants could rescue residual PAH activity and restore normal function. Co-expression of a single guide RNA plasmid, a FokI-dCas9-zsGreen1 plasmid, and the presence of a single-stranded oligodeoxynucleotide in PAH_c.1222C>T COS-7 cells - an in vitro model for PKU - corrected the PAH variant and restored PAH activity. Also in this system, the HDR enhancer RS-1 improved correction efficiency. This proof-of-concept indicates the potential of the FokI-dCas9 system for precision medicine, in particular for targeting PKU and other monogenic metabolic diseases.